The City Under Pressure: How Do Local Elites Perceive the Challenges of Public Management? - Cukier-Syguła, Monika (Journal of Public Governance, 2025)
Objective: The aim of the article is to assess and compare the perceptions of the most important socioeconomic challenges by the political elites of district towns in the Silesian Province. Research Design & Methods: Based on surveys conducted among representatives of local governments, differences in the perception of issues such as unemployment, housing shortages, financial difficulties, the state of the natural environment, the decline of heavy industry, and challenges related to public management were analysed. Using the Kruskal-Wallis test and post hoc analysis, a statistically significant difference in the perception of these problems between cities was found. Findings: The results suggest that these differences are due to the local historical, social, and economic conditions. Cities particularly affected by restructuring processes – such as Bytom, Świętochłowice, and Zabrze – feel the problems of unemployment and social exclusion more acutely, while more organisationally stable entities – such as Tychy and Bielsko-Biała – perceive management difficulties to a lesser extent. On the other hand, growing environmental awareness in some cities reflects changing local political priorities. Implications / Recommendations: The findings of the study highlight the need for individualised urban development strategies and a flexible system of public support that takes into account the different needs and capabilities of individual local government units. Contribution / Value Added: The article is part of a series of studies on public management and local development that emphasis